2011
DOI: 10.14499/indonesianjcanchemoprev2iss1pp173-181
|View full text |Cite
|
Sign up to set email alerts
|

An Extract of Zingiber officinale and Piper retrofractum Combination and Its Effect to Cancer Cell Line

Abstract: Chemotherapy may emerge side-effect since it may treat inconveniently the synthesis of nucleic acids and proteins, both cancer cells or normal cells. Plants as a cancer therapy were expected to reduce this toxicity and side effects. Plants which used empirically for cancer therapy was Zingiber officinale cv. Rubrum and Piper retrofractum. This study was conducted to examine the cytotoxic activity of ethanolic extract combination of two plants in HeLa and T47D cell lines. Zingiber officinale cv. Rubrum, Piper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The results showed increased cytotoxic activity against HeLa and T47D cells when the two ingredients were combined, with smaller IC50 values for the two test cells, namely 33 µg/mL and 53 µg/mL. [31] Compound that role play in the cytotoxic activity of this plant is piperine (alkaloid group). The piperin can protect cells from cancer by binding to proteins in mitochondria and triggering apoptosis without damaging normal cells, through increased activity of antioxidant enzymes such as superoxide dismutase, catalase, and glutathione peroxidase.…”
Section: Cytotoxic Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed increased cytotoxic activity against HeLa and T47D cells when the two ingredients were combined, with smaller IC50 values for the two test cells, namely 33 µg/mL and 53 µg/mL. [31] Compound that role play in the cytotoxic activity of this plant is piperine (alkaloid group). The piperin can protect cells from cancer by binding to proteins in mitochondria and triggering apoptosis without damaging normal cells, through increased activity of antioxidant enzymes such as superoxide dismutase, catalase, and glutathione peroxidase.…”
Section: Cytotoxic Activitymentioning
confidence: 98%
“…Based on research conducted by Ekowati et al (2011), it is known that 96% ethanol extract of Javanese long pepper fruit had cytotoxic activity against HeLa cells with an IC50 value of 47.409 µg/mL and against T47D with an IC50 value of 92.38 µg/mL. Ekowati et al, (2011) also combined this extract with red ginger rhizome. The results showed increased cytotoxic activity against HeLa and T47D cells when the two ingredients were combined, with smaller IC50 values for the two test cells, namely 33 µg/mL and 53 µg/mL.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Other results reported that increase concentrations of ginger extract led to increasing of the percentage inhibition of T47D cell growth. At a concentration of 62.5 (µg/mL), red ginger rhizome extract inhibited the growth of T47D cells to 32% Ekowati et al (2011). Nakagawa et al (2011), studied the6 diallyl disulfide may be a useful anticancer agent for management of human breast cancer.…”
Section: Garlic Fenps Ginger Fenpsmentioning
confidence: 99%
“…Minyak atsiri mengandung zat aktif yang mempunyai khasiat mencegah dan mengobati beberapa penyakit, baik yang ringan maupun penyakit berat, misalnya: masuk angin, pusing, rematik, mual-mual, impoten, kanker, maupun penyakit jantung (Aryanta, 2019). Identifikasi terdapat senyawa kimia dalam ekstrak jahe merah dan cabai jawa yang mengandung senyawa aktif berkhasiat untuk penyakit kanker (Ekowati et al, 2011). Dalam bidang makanan, saat ini dikenal berbagai jenis olahan jahe, misal permen jahe, manisan jahe, minuman instan, asinan jahe, kopi jahe, sirup jahe, dan beberapa produk olahan lain (Koswara & Diniari, 2016).…”
unclassified